Passive Monitoring Software Tool for Evaluation of Deployed WirelessHART Networks - Kunzel, Gustavo; Winter, Jean M.; Muller, Ivan; Pereira, Carlos E.; Netto, João C. (Anais do Simpósio Brasileiro de Engenharia de Sistemas Computacionais (SBESC); 2012: Anais do II Simpósio Brasileiro de Engenharia de Sistemas Computacionais, 2012)
Deployment of Wireless Sensor Networks in real-world control and monitoring applications may reveal performance problems caused by several factors. To track down such problems, it is necessary to inspect the conditions of network and nodes after deployment. In this paper, we discuss a monitoring software architecture for inspection of WirelessHART networks. Capture of information is done in a passive way using sniffers deployed in the network area. Messages are decoded, decrypted, filtered and then visualized in a graphic interface. A WirelessHART network was deployed in a laboratory for performance evaluation using the developed tool.